Fractured : race, class, gender and the hatred of identity politics - Richmond, Michael, 1986-; Charnley, Alex (Pluto Press, 2022)
Identity politics has smeared political discourse for over a decade. The right use it to lament the loss of free speech, while many on the left bemoan that it will be the end of class politics. It has been used to dismiss movements such as Black Lives Matter and brought seemingly progressive people into the path of fascism. It has armed the march of the transphobes. In Fractured, the authors move away from the identity politics debate. Instead of crudely categorising race, gender and sexuality as 'identities', or forcing them under the heading of'diversity', they argue that the interconnectedness of these groupings has always been inseparable from the history of class struggle under British and American capitalism. Through an appraisal of pivotal historical moments in Britain and the US, and a sharp look at contemporary debates, the authors tame the frenzied culture war, offering a refreshing and reasoned way to understand how class struggle is formed and creating the possibilities for new forms of solidarity in an increasingly fractured world.